Методы одномерного поиска - Северин, Валерий Петрович; Никулина, Елена Николаевна (НТУ "ХПИ", 2013)
Описаны лабораторные работы для изучения методов одномерного поиска. Даны теоретические основы методов и их рекомендуемые алгоритмы, варианты заданий для лабораторных работ, предложен порядок выполнения работ. Приведен справочный материал, включающий основы программирования методов оптимизации, даны примеры выполнения лабораторных работ. Предназначено для студентов технических специальностей.

Laboratory work for studying the methods of one-dimensional search is described. Theoretical bases of methods and their recommended algorithms, variants of tasks for laboratory works are given, the order of performance of works is offered. Reference material, which includes the fundamentals of programming optimization methods, is given, examples of the performance of laboratory work are given. It is intended for students of technical specialties.
Methods of one-dimensional search
Keywords: методы оптимизации; одномерный поиск; алгоритмы одномерной оптимизации; метод золотого сечения; метод дихотомии; лабораторные работы; optimization methods; one-dimensional search; one-dimensional optimization algorithms; golden section method; dichotomy method; laboratory works